الأمن الثقافي الرقمي: الأدبيات الميكانيزمات في زمن العولمة - مسعودي, احمد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
تهدف هذه الورقة البحثية إلى تشخيص واقع الأمن الثقافي في ظل البعد الرقمي للعولمة، و تحديد الكيفية الأمثل لتخفيض أكبر قدر ممكن من تهديدات و مخاطر التكنلوجيا و الرقمية على الخصوصيات الثقافية و كشف المتغير الفارق الذي من شأنه أن يجعل من تلك التهديدات و المخاطر مصدر فرص و مكاسب في سبيل تحقيق معادلة "ثقافة رقمية آمنة"، من أجل ذلك تم الإعتماد على المنهج الوصفي التحليلي، ليتبين بأن الإعتماد على الشراكة و الشفافية بين الفاعلين في عملية التأمين الثقافي الرقمي على مختلف المستويات (الدولاتية و غير الدولاتية، الرسمية و غير الرسمية) في إطار معايير الحوكمة. This research paper aims to diagnose the reality of cultural security in light of the digital dimension of globalization, and to determine the best way to reduce the largest possible number of technological and digital threats and risks to cultural specificities and to uncover the differential variable that makes these threats and risks a source of opportunities and gains in order to achieve the equation of a "safe digital culture". For this reason, the descriptive and analytical approach was relied upon, to show that reliance on partnership and transparency between the actors in the digital cultural insurance process at various levels (state and non-state, official and unofficial) in Governance Standards Framework.